Skate And BMX Park Centre Kota Serang - Nuroctaviani, Mentari Khanza, Ir. Indrawati, MT (2017)
Skateboard and BMX are extreme sports that are much loved youth today. This sport is very pumped adrenaline and tend to display speed, height, danger and action that takes courage. In the city of Serang, the phenomenon of fans of this sport starts of children, youth, adulthood. Sports enthusiasts every year increases, in 2016 the sport of skateboarding enthusiasts numbered 78 people and BMX bicycles amounted to 170 people. Some athletes quite many achievements ranging from local to international competition. However, serang city not yet have the means to practice this extreme sport. The fans and athletes often use the road ahead and rooftop plaza building RTC market. Presence " skate and bmx center" is expected to provide facilities with adequate facilities to accommodate fans of this extreme sport. The existence of Skate and BMX park center can be used as a means of recreation, training and competition. Parents and local residents can also take a stroll in the garden area available. Their sitting place useless to each other can also chat and discuss. By looking at these problems research held against the construction of a skatepark in the city of Serang. The study aims to identify development opportunities skatepark in the city of Serang. The study was conducted by the method of phenomenological views of the development of extreme sports in the city of Serang. The research method is qualitative, ie descriptive and comparative. Descriptive used to explain the problem, while comparative used to do a comparison with existing skatepark so that it can serve as a reference design as needed. Based on the analysis that has been made known many places that are not supposed to be a place to practice because it can interfere with surrounding activities. Therefore, along with the development of extreme sports for the next few years is considered Serang require extreme sports facilities that can accommodate and facilitate these activities. It is expected the Skate and BMX park center is able to support all activities of the extreme nature olahaga recreation and competition with national standards.